Propofol Exposure in Early Life Induced Developmental Impairments in the Mouse Cerebellum - Xiao, Rui; Yu, Dan; Li, Xin; Huang, Jing; Jing, Sheng; Bao, Xiaohang; Yang, Tiande; Fan, Xiaotang (Frontiers in Cellular Neuroscience, 2017)
Propofol is a widely used anesthetic in the clinic while several studies have demonstrated that propofol exposure may cause neurotoxicity in the developing brain. However, the effects of early propofol exposure on cerebellar development are not well understood. Propofol (30 or 60 mg/kg) was administered to mice on postnatal day (P)7; Purkinje cell dendritogenesis and Bergmann glial cell development were evaluated on P8, and granule neuron migration was analyzed on P10. The results indicated that exposure to propofol on P7 resulted in a significant reduction in calbindin-labeled Purkinje cells and their dendrite length. Furthermore, propofol induced impairments in Bergmann glia development, which might be involved in the delay of granule neuron migration from the external granular layer to the internal granular layer during P8 to P10 at the 60 mg/kg dosage, but not at the 30 mg/kg dosage. Several reports have suggested that the Notch signaling pathway plays instructive roles in the morphogenesis of Bergmann glia. Here, it was revealed that propofol treatment decreased Jagged1 and Notch1 protein levels in the cerebellum on P8. Taken together, exposure to propofol during the neonatal period impairs Bergmann glia development and may therefore lead to cerebellum development defects. Our results may aid in the understanding of the neurotoxic effects of propofol when administrated to infants.